Pengembangan Media Pembelajaran Berbasis Augmented Reality Pada Pembelajaran Matematika di Kelas VI Sekolah Dasar - Nurjasriati Nurjasriati; Melva Zainil (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This research addresses the limited variety of engaging learning media in elementary school mathematics, which has not optimally supported active student involvement in the learning process. Therefore, this study aimed to develop Augmented Reality based learning media that are valid, practical, and effective for sixth grade mathematics learning. The study employed a research and development approach consisting of the stages of analysis, design, development, implementation, and evaluation. The participants were sixth grade students from three public elementary schools in the Sumpur Kudus District. Data were collected using expert validation sheets, practicality questionnaires for teachers and students, and pretest and posttest instruments to measure learning effectiveness. Data analysis focused on validity, practicality, and effectiveness criteria. The analysis stage revealed low student engagement caused by teacher centered instruction and less attractive learning media. The design stage produced a learning media prototype and a user guide adapted to student characteristics. The development stage showed that the material aspect achieved a validity score of 96 percent, the media aspect achieved 80 percent, and the language aspect achieved 96 percent. Implementation results indicated very high practicality, with a score of 100 percent from teachers and 92.28 percent from students. Evaluation results demonstrated an effectiveness score of 80.02 percent, with average learning outcomes increasing from 50.95 before implementation to 88.70 after implementation. Overall, the findings indicate that Augmented Reality based mathematics learning media are feasible and effective, inviting readers to consider their broader application in improving student engagement and learning outcomes.